1987
DOI: 10.1007/bf00014906
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a soybean ?-conclycinin gene under the control of the Cauliflower Mosaic Virus 35S and 19S promoters in transformed petunia tissues

Abstract: A gene encoding the α'-subunit of β-conglycinin was ligated to the 19S and 35S promoters of Cauliflower Mosaic Virus and introduced into petunia plants on a disarmed Ti-plasmid using Agrobacterium tumefaciens. Transformed cells were regenerated into whole plants and ummunoreactive polypeptides and hybridizable, polyadenylated mRNA were detected in transformed tissues. Expression from the 35S promoter was 10 to 50 times greater than expression from the 19S promoter. The level of immunodetectable polypeptides wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

1989
1989
2012
2012

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(21 citation statements)
references
References 32 publications
2
18
0
1
Order By: Relevance
“…This result is similar to that in an earlier report, where it was shown that the expression level in individual transformants varied even at identical gene copy number (24). The 35-kDa AmA1 protein was detected in both pSB8 and pSB8G immunoblots ( Fig.…”
Section: Immunodetection Of Ama1 Protein In Transgenic Tuberssupporting
confidence: 92%
“…This result is similar to that in an earlier report, where it was shown that the expression level in individual transformants varied even at identical gene copy number (24). The 35-kDa AmA1 protein was detected in both pSB8 and pSB8G immunoblots ( Fig.…”
Section: Immunodetection Of Ama1 Protein In Transgenic Tuberssupporting
confidence: 92%
“…The CaMV 19s promoter directs the production of an abundant subgenomic mRNA encoding a protein that is both a major structural component of the cytosolic inclusion bodies and a translational activator for the polycistronic 35s RNA (Bonneville et al, 1989;Gowda et al, 1989). Although the CaMV 19s promoter is a strong promoter, it is reportedly 10-to 50-fold less active than the CaMV 35s promoter (Lawton et al, 1987). The CaMV 35s promoter directs the production of a terminally redundant transcript that is 180 nucleotides greater than genome length.…”
Section: Introductionmentioning
confidence: 99%
“…Although exceptions exist, several studies have shown that seed storage proteins are generally significantly less stable in the vegetative versus the seed tissues of a foreign host (Lawton et al 1987;Bagga et al 1992;Higgins and Spencer 1991;Nakamura et al 1993; but see also Utsumi et al 1993). For example, despite similar levels of 13-conglycinin mRNA in the leaves and seeds of transgenic petunia (utilizing a constitutive viral promoter to drive expression), the leaf cell environment yields a much lower level of protein accumulation (e.g., by 30-fold for the a'-subunit) (Lawton et al 1987;Nakamura et al 1993).…”
Section: Discussionmentioning
confidence: 94%
“…The low levels of accumulation of seed storage proteins observed in the transgenic host leaves, compared with the seed, even when the genes contain the cauliflower mosaic virus (CaMV) 35S promoter Lawton et al 1987;Bagga et al 1992;Nakamura et al 1993), may result from the continuous breakdown of the proteins in the protease-rich vacuoles of the leaves (Wandelt et al 1992). Differential proteolytic processing of storage proteins, yielding polypeptides of variable length in these two tissues, has also been documented, although the precise relationship between this and a lack of protein stability in the leaf, due to proteolysis, is presently unclear.…”
Section: Introductionmentioning
confidence: 98%